Some System Problems of Russian Mining Enterprises of Ferrous Metallurgy - Samarina, Vera; Skufina, Tatiana; Samarin, Alexander; Baranov, Sergey (International Review of Management and Marketing, 2016)
The results of the original scientific research directed on the estimation of prospects and restrictions of activity of Russian ferrous metallurgy mining enterprises under present-day conditions have been presented in the article. It has been shown that ferrous metallurgy branch is one of traditional indicators of economic development of the country. The place of ferrous metallurgy among other Russian industries has been identified. The place of Russian ferrous metallurgy enterprises in the world production structure has been shown. The estimation of iron ore reserves which are supervised by leading world companies of ferrous metallurgy has been given. Some objective and subjective branch problems of the mining enterprises of ferrous metallurgy have been revealed. Such system problems of Russian metallurgical complex as low power and ecological efficiency have been identified. Keywords: mining enterprises, ferrous metallurgy, metal production JEL Classifications: L61; L71; P13; P42